Evaluation of Work-Related Deaths in Geriatric Population - Bölükbaşı, Hacı Seyit; Tecir, Çağnur Canatan; Şengül, Niyazi Burak; Kırcı, Güven Seçkin; Özer, Erdal (The Bulletin of Legal Medicine, 2024)
Objective: Worker fatalities is a concept that encompasses all deaths occurring during the execution of a profession, which is undertaken to sustain a person’s livelihood, due to the physical and psychological effects of the work. The aim of this study is to examine various parameters in cases aged 65 and over, aiming to reveal the level, form, and causes of occupational accidents and fatalities in the geriatric population. Through this, the study aims to contribute to the literature by shedding light on the exposure level, form, and causes of occupational accidents and fatalities among the geriatric population. Methods: In this cross-sectional, descriptive study, a retrospective analysis was conducted on 86 cases of work-related deaths among the population aged 65 and over in Turkey in 2020, which were reported in the national print and visual media. Results: Of the examined 86 worker fatalities, it was found that 77.9% (n=67) were in the age range of 65-74 years, 88.4% (n=76) of the cases were male, and accidents were the leading cause of death in 72.1% (n=62) of cases. When examined in terms of location distribution, it was found that 43.0% (n=37) occurred in rural areas. Conclusion: In our country, the number of individuals in the geriatric population participating in the workforce is higher compared to developed countries. Consequently, occupational fatalities among the geriatric workforce are also higher. Policies implemented in Europe and America for the aging workforce should be observed, and regular health check-ups should be ensured.